STRENGTHENING GOVERNMENT ORGANIZATIONAL CULTURE IN THE ERA OF REGIONAL AUTONOMY - Mansyur, Makbul (Jurnal Multidisiplin Sahombu, 2023)
This study aims to strengthen organizational culture in local government in the era of regional autonomy. This study used a qualitative approach with a case study method. The results showed that a strong organizational culture is a key factor in improving local government performance. A strong organizational culture is defined as the adoption of shared values, traditions and norms that are understood and carried out by all members of the organization. As for the role of a strong organizational culture towards the organization, members of the organization and those related to the organization, namely organizational identity, unifying the organization and conflict resolution. It is hoped that the results of this research can become input for local governments in developing and strengthening organizational culture to improve local government performance in the future.